2005
DOI: 10.1088/0741-3335/47/12/001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the direction of plasma vertical movement during major disruptions in ITER

Abstract: The plasma movement in the upward direction (away from the X-point) after the thermal quench (TQ) of major disruptions in ITER is favourable for the machine design, since the downward movement causes larger electromagnetic (EM) load due to the induced eddy and halo currents. Vertical directions of plasma movement after the TQ in ITER are investigated using the predictive mode of the DINA code. Three dominant parameters in determining the direction of plasma movement are identified: (i) the rate of plasma curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…It is known [2][3][4][5]7,8,[10][11][12][13][14][15][16][17]20,22,[33][34][35][36][37] that the force on the wall during the disruptions in tokamaks depends on the halo current, which is the part of the plasma current that flows in the conducting structure and has a return path through the plasma. 14,15,22,33,34 In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It is known [2][3][4][5]7,8,[10][11][12][13][14][15][16][17]20,22,[33][34][35][36][37] that the force on the wall during the disruptions in tokamaks depends on the halo current, which is the part of the plasma current that flows in the conducting structure and has a return path through the plasma. 14,15,22,33,34 In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We attribute this change of direction to the stronger drop in l i (3) for case #2. It was found in [18] that large drops of the internal inductance during major disruptions in ITER lead to downward displacements. Similarly for the ASDEX-Upgrade tokamak [20], it was found that drops of l i in lower single-null plasmas cause a "vertical dragging effect" that moves the plasma downwards.…”
Section: Cq Phase Of Case #2mentioning
confidence: 99%
“…In these experiments, a rupture disk (RD) has been used to realize quick injections of gas. In addition, at the downstream of the RD, orifices of different diameters (6,12, and 45 mm) have been used to control the amount of the injected impurity gas. The current decay times τ c for each RD have been fitted with an exponential curve using 80% to 20% of I p0 (cf.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…employing the NP of the plasma current center. Since there is no universal NP [6], however, the halo current should be decreased during a VDE, in particular caused by a slow current quench. In DIII-D, a reduction of the halo current was observed by shutting down the plasma very quickly by means of a massive impurity injection [7].…”
Section: Introductionmentioning
confidence: 99%